Agency Theory and Value of Agro -Allied Firm in Nigeria - Udeh, E.F (Research Parks Publishers, 2024)
This study evaluates relationships between agency theory and firm value of quoted Agro- Allied firm in Nigeria. The levin, Lin and Chu (LLC) model was used in analysis for panel unit root, while Johnson’s Co –integration tested for long run relationship of variables. Other tests conducted include Error correction model and Pair wise Granger causality which were all employed in processing ex-post panel data obtained from the Nigerian stock exchange for the period 2014 through 2021. Findings from results reveal that Agency cost has a significant and positive relationship with both dependent variables and also shows evidence of long run relationship. As such, the study concludes that agency Cost has an impact on firm value, and recommends that shareholders should be pro active in dealing with agency problems by resolving conflicts with the least possible agency cost ,and also formulate strategic guidelines to cut down on agency costs since optimality rests at the point where Agency cost is at the barest minimal and achieving this will obviously enhance firm value of Agro Allied firms in Nigeria.